2013
DOI: 10.1128/cvi.00352-13
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Highly Antigenic Region of Subtilisin-Like Serine Protease 1 for Serodiagnosis of Neospora caninum Infection

Abstract: Neospora caninum is an apicomplexan parasite that causes abortion in cattle; hence, accurate diagnosis of this pathogen is important to the cattle farming industry. Our previous proteomics and immunoscreening analyses revealed that the N. caninum subtilisin-like serine protease 1 (NcSUB1) has potential as a serodiagnostic tool for Neospora. Consequently, we expressed two fragments containing five NcSUB1 tandem repeat copies covering amino acids (aa) 524 to 843 (NcSUB1t) and 555 to 679 (NcSUB1tr) to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 18 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…They demonstrated that NcSUB1 is highly conserved in N. caninum and have only 63% sequence identity to the T. gondii orthologue. Therefore, they demonstrated no cross-react with T. gondii in their ELISA method [35]. Hruzik et al introduced Cterminal domain of TgSUB1 as a potential marker for serodiagnosis of acute toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…They demonstrated that NcSUB1 is highly conserved in N. caninum and have only 63% sequence identity to the T. gondii orthologue. Therefore, they demonstrated no cross-react with T. gondii in their ELISA method [35]. Hruzik et al introduced Cterminal domain of TgSUB1 as a potential marker for serodiagnosis of acute toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Potentially useful markers for serodiagnosis are continuously being analyzed, and some recent studies have focused on the highly antigenic region of subtilisinlike serine protease 1 (Ybañez et al, 2013), NcSRS2 surface protein (Pinheiro et al, 2013), Neospora-surface antigen (p40) (He et al, 2013), monoclonal antibodies against NcSAG1 (Dong et al, 2013), and anti-rNcp-43 polyclonal antibodies (Sá et al, 2014), among others.…”
Section: Serological Tests In Diagnosing Bovine Neosporosismentioning
confidence: 99%
“…A protease with 42 kDa was localized in the rhoptry of T. gondii by means of a MAb; this MAb also reacted to a 42 kDa protein in N. caninum, which was also localized in the rhoptry of this parasite (Ahn et al 2001). (Howe et al 1998; T. gondii (Howe et al 2002;Chahan et al 2003;Liao et al 2005b;Huang et al 2007;Ybanez et al 2013) Sarcocystis spp. (Howe et al 2002) rNcSRS2 (Ba/SRS2p44, NcSRS2t, tNcSRS2) Surface (35-43 kDa) (Hemphill and Gottstein, 1996;Hemphill et al 1997;Howe et al 1998) T. gondii (Nishikawa et al 2001(Nishikawa et al , 2002Gaturaga et al 2005;Huang et al 2007;Liu et al 2007) H. heydorni (Nishikawa et al 2001 Surface (18 kDa Dense granules (68 kDa, 37 kDa) (Liddell et al 1998) T. gondii (Lally et al 1996;Jenkins et al 1997) Sarcocystis spp.…”
Section: Toxoplasma Gondii Vs N Caninummentioning
confidence: 99%